2011
DOI: 10.1016/j.exppara.2010.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral responses of Poecilia vivipara (Osteichthyies: Cyprinodontiformes) to experimental infections of Acanthocollaritrema umbilicatum (Digenea: Cryptogonimidae)

Abstract: The swimming behavior of Poecilia vivipara was evaluated using an image analysis system comparing laboratory-reared uninfected fish before and after experimental infection with different intensities of cercariae of the trematode Acanthocollaritrema umbilicatum. Two experiments were performed, each with 30 fish which were individually exposed to 30 and 50 cercariae, respectively, shed from experimentally infected molluscs, Heleobia australis. Before and after (17-27 days) infection, the behavior of each fish wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Both of these two trematodes are considered to have zoonotic potential. The new data will support future control measures to reduce the level of parasitism in P. vivipara when reared in fish farming systems, especially for aquarium purposes, but also for fish used as a model for toxicological and behavioural studies (Santos, Cunha & Santos 2011;Harayashiki et al 2013).…”
Section: Discussionmentioning
confidence: 85%
“…Both of these two trematodes are considered to have zoonotic potential. The new data will support future control measures to reduce the level of parasitism in P. vivipara when reared in fish farming systems, especially for aquarium purposes, but also for fish used as a model for toxicological and behavioural studies (Santos, Cunha & Santos 2011;Harayashiki et al 2013).…”
Section: Discussionmentioning
confidence: 85%
“…The image analysis biomonitoring system (IABS) was based on the use of a Videomex V ® (Columbus Instruments, Ohio, USA) using the software Travelled Distance of Multiple Objects after Magalhães et al (2007) and Santos et al (2011). The instrument includes a recording cabin made of acrylate, diffused soft lighting and an analogical video camera.…”
Section: Locomotory Activitymentioning
confidence: 99%
“…In the area of Rio de Janeiro, Brazil, the life cycles of digenean species have been elucidated in the ecosystem of the Rodrigo de Freitas lagoon [5-8] and maintained in our laboratory, enabling us to compare the swimming behaviour of an intermediate fish host before and after a digenean infection using an image analysis biomonitoring system [9]. Although the avian and fish fauna of the lagoon are well known, there are few studies on molluscs in this area [6], among which is the ‘red-rim melania’ Melanoides tuberculatus (Müller, 1774) (Thiaridae), an introduced gastropod snail which now has a wide geographical distribution throughout the Neotropics [10].…”
Section: Resultsmentioning
confidence: 99%
“…Melanoides tuberculatus infected with Centrocestus formosanus , in addition to a reduced movement, exhibited an irregular locomotory activity pattern, whereas uninfected snails had a regular pattern of locomotory activity during the biomonitoring period. A similar experiment by Santos et al [9], using a Videomex V® system, assessed the locomotory activity of fish hosts in the same lagoon, and these authors suggested that a lethargic and less motile parasitized fish is more likely to be preyed upon by the definitive host. In the case of the less motile snail host, we consider that it is more likely to influence the life cycle of C .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation